Internet and the Dynamics of Higher Education Institutions: the Role of Distance Learning – Case Studies in Senegalese Universities - (:unkn) unknown (My University, 2009)
This dissertation interrogates the way Information and Communication Technologies influence the evolution of higher education institutions in the context of an information society coupled with crisis in African higher education. In addition to analysing how the Internet affects the dynamics of these institutions, the author endeavours to understand its socio-cultural consequences. The thesis addresses a number of key issues: the 'developmentalist configuration' in Senegalese higher education; technology and model transfers; innovation in higher education; reforming an institution in crisis; and appropriating the post-colonial higher education institution. Beyond analysing the approaches to ICTs for Education proposed by the Association of Francophone Universities (AUF) and the African Virtual University (AVU), this research aims to define the role of ICTs, and of the Internet, in the reform of higher education institutions. The approaches advocated by the AUF and AVU necessarily impact tertiary education establishments, particularly now that they have their own ICT strategy and distance learning programs. To what extent do these organisations' examples promote innovation in Senegalese higher education? What characterises this technology/model transfer and how might it impact the course of institutional changes already underway? What are the consequences of externally focused technologies on the dynamics of higher education? These are some of the questions this PhD research aims to answer, in order to assess if higher education finally makes sense in senegalese society.
Keywords: African Research